2017
DOI: 10.1007/s00062-017-0598-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Circumferential Aneurysmal Wall Enhancement in Symptomatic Patients with Unruptured Intracranial Aneurysms: a High-resolution MRI Study

Abstract: Our study demonstrates that CAWE correlated with sentinel headaches and third nerve palsy caused by unruptured aneurysms, and this may be an additional clue to distinguish the cause of these symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…In another publication focusing on unruptured aneurysms only, circumferential aneurysm wall enhancement was observed more frequently in symptomatic (70%) than in asymptomatic (27%) aneurysms. 5 Patients with symptomatic aneurysms in that study had presented with either sentinel headaches or third nerve palsy. Occasionally, wall enhancement on VWI has been associated with inflammatory cell invasion in unruptured aneurysms, as shown by Larsen and colleagues using histological analysis.…”
Section: Discussionmentioning
confidence: 91%
“…In another publication focusing on unruptured aneurysms only, circumferential aneurysm wall enhancement was observed more frequently in symptomatic (70%) than in asymptomatic (27%) aneurysms. 5 Patients with symptomatic aneurysms in that study had presented with either sentinel headaches or third nerve palsy. Occasionally, wall enhancement on VWI has been associated with inflammatory cell invasion in unruptured aneurysms, as shown by Larsen and colleagues using histological analysis.…”
Section: Discussionmentioning
confidence: 91%
“…In total, 53 aneurysms were classified as unstable at aneurysm wall enhancement has the potential to provide an additional, individual-based indicator of aneurysm stability. For instance, CAWE, which has both thin (grade 2) and thick (grade 3) circumferential enhancement, has been associated with instability (7)(8)(9)(10)15,16) but also with low specificity. On the basis of a thorough evaluation of enhancement patterns, we devised a four-grade classification aimed at evaluating their relative accuracies in identifying unstable aneurysms and demonstrated that the highest grade of vessel-wall MR enhancement according to this classification had a high specificity to distinguish stable from unstable aneurysms with potential direct implications in patient management.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with subarachnoid hemor-rhage and multiple aneurysms, MR imaging can help discriminate the responsible aneurysm. Fu et al 2 proposed that circumferential aneurysmal wall enhancement on high-resolution MR vessel wall imaging (HR-VWI) is correlated with headaches and third nerve palsy caused by unruptured aneurysms. Two previous studies indicated that as an indicator of inflammation, the aneurysm wall enhancement on HR-VWI postgadolinium T1WI has the potential for discriminating unstable aneurysms from stable ones.…”
mentioning
confidence: 99%